Seasonal and spatial variations of dissolved organic matter biodegradation along the aquatic continuum in the southern taiga bog complex, Western Siberia - Raudina, Tatiana V.; Smirnov, Sergey V.; Lushchaeva, Inna V.; Istigechev, Georgy I.; Kulizhsky, Sergey P.; Golovatskaya, Evgeniya A.; Shirokova, Liudmila S.; Pokrovsky, Oleg S. (Water)
The inland aquatic ecosystems play a significant role in the global carbon cycle, owing to the metabolism of terrestrially derived organic matter as it moves through fluvial networks along the water continuum. During this transport, dissolved organic matter (DOM) is microbial processed and released into the atmosphere, but the degree and intensity of this processing vary greatly both spatially and temporally. The Western Siberian Lowlands is of particular interest for a quantitative assessment of DOM biodegradation potential because the global areal-scale effects of DOM biodegradation in abundant surface organic-rich waters might be the highest in this region. To this end, we collected water samples along a typical aquatic continuum of the Bakchar Bog (the north-eastern part of the Great Vasyugan Mire) and, following standardized protocol, conducted an experimental study aimed at characterizing the seasonal and spatial variability of dissolved organic carbon (DOC) biodegradability. The biodegradable DOC fraction (BDOC) over the exposure incubation period ranged from 2% to 25%. The natural aquatic continuum “mire–forest–stream–river” demonstrated the systematic evolution of biodegradable DOC among the sites and across the seasons. The highest biodegradation rates were measured during spring flood in May and decreased along the continuum. The maximum possible CO2 production from DOM yielded the maximum possible flux in the range of 0.1 and 0.2 g C-CO2 m−2 day−1 d, which is an order of magnitude lower than the actual net CO2 emissions from the inland waters of the WSL. This study suggests that although the biodegradation of the humic waters of the WSL can sizably modify the concentration and nature of the DOM along the aquatic continuum, it plays only a subordinary role in overall C emissions from the lakes and rivers of the region.